The Kabbalistic “Teaching Panel” of Princess Antonia: Divine Knowledge for Both Experts and Laity - Morlok, Elke (Church history and religious culture, 2018)
This article explores the complex interweaving of kabbalistic and Christological concepts within the kabbalistic “teaching panel” (Lehrtafel) of Princess Antonia of Württemberg. The essay discusses the artwork in the context of visual representations of the ten sefirot, the divine attributes or vessels in Jewish mysticism. Executed as an altarpiece for the church in Bad Teinach in Southern Germany, the work integrates the sefirot into a pansophic concept that served devotional and educational purposes with a salvific goal. The article argues that, with the Lehrtafel, Antonia and her teachers created a devotional object that could be accessed by both regular Christian laity and experts who possessed deeper knowledge of Kabbalah.